THE PHENOMENON OF UKRAINIANNESS THROUGH THE PRISM OF RESEARCHS OF THE CENTER OF UKRAINIAN STUDIES OF THE TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV - Воропаева, Татьяна (SWorldJournal, 2020)
The article is dedicated to the 20th anniversary of the Center for Ukrainian Studies of Taras Shevchenko National University of Kyiv. The author highlights the features of the phenomenon of Ukrainian heritage through the prism of figures and events. The